People’s Behavior towards the Celebration of the Eucharist in the Catholic Church - Yohanes Driyanto; Yasintha Soelasih (Universitas Negeri Semarang, 2024)
Food is a must for human being. It is analog with the Eucharist for the Catholics. Based on the belief, therefore, this research is intended to see the attitude of the people and the teachings obtained in the celebration of Eucharist in shaping individual behavior. There are two characteristics of attitudes, positive and negative. The positives encourage the faithful to have fuller awareness and more active participation in the celebration. The negatives create in the heart and mind of them a kind of reluctance and compulsion in having it. To support the results of this research, it was conducted with qualitative and quantitative methods respectively. The first was done by focus group discussion (FGD) and the second by 222 respondents giving their answers to the questionnaire online. Smart-PLS tools were used as research instruments and to address the problems studied. There are seven hypotheses formed by the problems and the results accepted are only one: a positive attitude towards the Eucharist influences individual behavior in the Eucharist. The attitude encourages the Catholics to get more involved in the celebration. This research contributes to the formation of the Catholics in having the celebration of the Eucharist in Catholic Church.